Blockade of stress-induced increase of glutamate release in the rat prefrontal/frontal cortex by agomelatine involves synergy between melatonergic and 5-HT(2C )receptor-dependent pathways - Tardito, Daniela (BioMed Central, 2010)
BACKGROUND: Agomelatine is a melatonergic receptor agonist and a 5HT(2C )receptor antagonist that has shown antidepressant efficacy. In order to analyze separately the effect of the two receptorial components, rats were chronically treated with agomelatine, melatonin (endogenous melatonergic agonist), or S32006 (5-HT(2C )antagonist), and then subjected to acute footshock-stress. RESULTS: Only chronic agomelatine, but not melatonin or S32006, completely prevented the stress-induced increase of glutamate release in the rat prefrontal/frontal cortex. CONCLUSIONS: These results suggest a potential synergy between melatonergic and serotonergic pathways in the action of agomelatine.